Analise de viabilidade técnica-econômica na substituição de um sistema combinado de geração de vapor-vácuo por bombas secas - Oliva, Robson Vitor [UNESP] (2013)
Traditional technologies used to generate vacuum for steelmaking are steam ejectors, liquid ring vacuum pumps and systems combined of them. The steam ejector system has a capacity to generate a medium vacuum 101 kPa (1 atm) a 0,1 Pa (0,01 mbar), the liquid ring pumps only reach 3 kPa (30 mbar) and dried pump cover the range of 101 kPa (1 atm) até 67 Pa (0,67 mbar), band required for use in secondary metallurgy and is the limit of this technology. In this work was realized a case study in the industrial sector that uses the vacuum generation through steam ejectors superheated at 250 ° C and 1,2 MPa (12 kgf/cm2). The vacuum is needed for removal of undesirable gases in the composition of the steel as nitrogen, oxygen, hydrogen and sulfur which causes weakness in the crystalline structure. Currently there have been technological innovations for vacuum generation in applications in VD (vacuum degassing), vacuums until to 67 Pa (0,67 mbar) and VOD (decarburization) for vacuums of 8-20 kPa (80-200 mbar). One of these innovations is mechanical pumps dried formed by three-stage vacuum, joining various technologies, the first and second rotor roots and the third screw rotor. In this study the objective was to measure the real returns offered by the steam ejector system, along with the performance of the boiler compared to the new dry pump technology in steel making industry, will present the advantages, disadvantages and cost effective to replace the vacuum generating system. Representing a 92,7% reduction in energy consumption and 81,4 % reduction in operating costs